Design of online transaction model on traditional industry in order to increase turnover and benefits - Abadi, Satria; Huda, Miftachul; Hehsan, Aminudin; Marzuki Mohamad, Ahmad; Basiron, Bushrah; Suhaila Ihwani, Siti; Azmi Jasmi, Kamarul; Safar, Jimaain; Kilani Mohamed, Ahmad; Hassan Wan Embong, Wan; Shakib Mohd Noor, Sulaiman; Brahmono, Boris; et al. (International Journal of Engineering and Technology, 2018)
Online transactions are transactions made sellers and buyers online through the Internet media, there is no direct encounter between buyers and sellers. Currently with the rapid development of technology and the Internet in Indonesia, has had a great impact on the change of industrial business. That is starting from the way advertising, buying and selling, how to interact between humans, and so forth. With e-commerce has changed a lot in the process of buying and selling. Panda Alami is one of the banana chips industry established since 1998 in Cipadang Pesawaran village. This banana chips industry still uses manual way in transaction process. To increase the turnover and profit that is the purpose of this study, the transaction model is developed with SDLC (System Development Life Cycle) and software used to design and design this application is PHP programming language, MySQL Database and Adobe Photoshop CS3. Features include product search, order, delivery and payment confirmation and thus provide integration of the entire inventory unit sales network. An equally important factor is trust. In this process trust is the main capital. Because without the trust of both parties, then the process of online transactions can not happen and done.Â Â